European Breeding Bird Declines Associated With Narrower Climatic Niches - Karolina Zalewska; James J. Gilroy; Inês Catry; Philip W. Atkinson; Alena Klvaňová; Aldina M. A. Franco (Journal of Biogeography, 2025)
Aim Anthropogenic climate change has increasingly been identified as a major threat to global biodiversity. However, the extent of this threat is likely to be uneven across species, due to differences in life histories or exposure to environmental change. The range of climatic conditions a species experiences across its range extent, known as the realised climatic niche, may be an indicator of species resilience to climate change. Species with large range extents, occurring across diverse climatic conditions, are expected to be less affected by climate change due to lower physiological constraints and tolerance to a wider range of climates. However, this may not be the case if local populations are adapted to specific environmental conditions. In this study, we investigate whether the extent of the species' realised climatic niche, also known as the climatic niche breadth, is linked to their long‐term population trends. Location Europe. Taxon Birds. Methods We extract climate data across the breeding‐only and resident ranges of 159 European bird species and use an ordination method to produce a representation of the species climatic niches. We then relate the niche breadth of each species to their range area and incorporate this relationship, along with the species' diet, main habitat type, migratory status and average body mass, to investigate their relationship with the species long‐term population trend. Results Species with small range areas showed larger variation in climatic niche breadth than species with larger ranges. For species with similar range areas, those with broader climatic tolerance were less likely to be declining than those with narrow climatic niches. Main Conclusions These findings can help us understand the threats associated with climate change and allow for rapid assessment of the importance of climatic factors on population trends, providing an invaluable tool for targeting habitat conservation.